THE ROLE OF MORAL AND LEGAL EDUCATION IN THE FORMATION OF CIVIC QUALITIES OF A PERSON (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article examines the role of moral and legal education and upbringing in the formation of civic qualities of the younger generation. The need to create an integrated system of moral and legal education for young people at all levels of the educational process is emphasized.